2020
DOI: 10.1097/ftd.0000000000000741
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis of Meropenem in Critically Ill Patients With Acute Kidney Injury Treated With Continuous Hemodiafiltration

Abstract: Background: The aim of this study was to conduct a population pharmacokinetic (PK) analysis of meropenem and to explore the optimal dosing strategy for meropenem in critically ill patients with acute kidney injury receiving treatment with continuous hemodiafiltration (CHDF). Methods: Blood samples were obtained on days 1, 2, and 5 after the start of meropenem administration, immediately before dosing, and at 1, 2, 6, and 8 hours after dosing. Population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Six of the studies enrolled only subjects on renal replacement therapy. The most commonly reported covariate on meropenem clearance was CL CR as a covariate on total or renal clearance (in 8 of 11 studies that included patients not on renal replacement therapy), [70][71][72][73][74][75][76][77][78] in agreement with meropenem being primarily cleared by urinary excretion.…”
Section: Complexities Associated With Antibiotic Therapy In Patients mentioning
confidence: 99%
“…Six of the studies enrolled only subjects on renal replacement therapy. The most commonly reported covariate on meropenem clearance was CL CR as a covariate on total or renal clearance (in 8 of 11 studies that included patients not on renal replacement therapy), [70][71][72][73][74][75][76][77][78] in agreement with meropenem being primarily cleared by urinary excretion.…”
Section: Complexities Associated With Antibiotic Therapy In Patients mentioning
confidence: 99%
“…Only the model by Burger et al 2018 ( 24 ) included total flow rate as a structural covariate on clearance. Further covariates for clearance were described by either residual diuresis in two models (O’Jeanson et al [ 8 ] and Ulldemolins et al [ 25 ]) or eGFR in two models (Niibe et al 2022 [ 26 ] and Hanberg et al [ 27 ]). Nevertheless, most models ( n = 6) included only one significant covariate.…”
Section: Resultsmentioning
confidence: 99%
“…S7 and S9, Table S8). The models by Shekar et al 2014 ( 28 ), Burger et al 2018 ( 24 ), Grensemann et al 2020 ( 29 ), and Niibe et al 2020 ( 26 ) showed no bias in the goodness-of-fit (GOF) plots ( Fig. 1 ) and an accuracy and precision of MPE |20%| and MAPE of <35%, respectively, whereas the models by Onichimowski et al 2020 ( 30 ) and Hanberg et al 2018 ( 27 ) showed a strong visual bias in the GOF plots, a MAPE of >90% and a misfit in the pcVPCs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations